PENGOLAHAN BAHAN PUSTAKA DI SMP NEGERI 8 PONTIANAK - Khairiah, Rifka; Latifa Hanum, Atiqa Nur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe title of this final project is â€œThe Library Collection Arrangement in SMP Negeri 8 Pontianakâ€. This research looks at the arrangement of library materials in SMP Negeri 8 Pontianak, where the purpose is to show the classification procedure, cataloging, and the way to search for information. The research method used by the researcher in this final project fulfillment was the descriptive method with qualitative approach. The data collection techniques were observation, interview, and documenting that had done by the researcher to the informant. The result of this research is that the classification done on the collection is appropriate but the collection of fiction classification is not appropriate, the classification using the symbol of the letter F. On the catalog can only be traced by the officer alone should also be used by pemustaka existing in SMP Negeri 8 Pontianak, it means in information tracking is still not optimal.Â Â Â Â Â Â Â Â  Keywords: Classification, Cataloging, Information SearchÂ